The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1152/ajpcell.00278.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis transmembrane conductance regulator contributes to reacidification of alkalinized lysosomes in RPE cells

Abstract: The role of the cystic fibrosis transmembrane conductance regulator (CFTR) in lysosomal acidification has been difficult to determine. We demonstrate here that CFTR contributes more to the reacidification of lysosomes from an elevated pH than to baseline pH maintenance. Lysosomal alkalinization is increasingly recognized as a factor in diseases of accumulation, and we previously showed that cAMP reacidified alkalinized lysosomes in retinal pigmented epithelial (RPE) cells. As the influx of anions to electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 37 publications
3
53
0
Order By: Relevance
“…Thus, Barasch et al demonstrated a regulation of the pH in trans-Golgi vesicles by CFTR and an alkalinization of these vesicles in cells lacking CFTR (28). Several more recent studies revealed that Cftr also contributes to acidification of phagolysosomes in macrophages (20,29,(34)(35)(36). These studies showed that Cftr determines the influx of chloride ions into lysosomes (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Barasch et al demonstrated a regulation of the pH in trans-Golgi vesicles by CFTR and an alkalinization of these vesicles in cells lacking CFTR (28). Several more recent studies revealed that Cftr also contributes to acidification of phagolysosomes in macrophages (20,29,(34)(35)(36). These studies showed that Cftr determines the influx of chloride ions into lysosomes (29).…”
Section: Discussionmentioning
confidence: 99%
“…The negatively charged chloride ions serve as counterions for protons pumped into phagolysosomes by the lysosomal V-type H ϩ -ATPase (37,38). A lack of Cftr thereby prevents the accumulation of protons in phagolysosomes and therefore impairs acidification of these vesicles, resulting in alkalinization of phagolysosomes (28,29,(34)(35)(36). Since the acidification of phagolysosomes is required for killing pathogens and the full activity of lysosomal enzymes, these studies concluded that the defect of Cftr-deficient alveolar macrophages to kill pathogens is caused by the increased pH in lysosomes in Cftr-deficient cells (29,36).…”
Section: Discussionmentioning
confidence: 99%
“…However, the granule pH data raise the possibility that finite amounts of CFTR are present in the secretory pathway/mucin granule membrane and play a role in granule acidification. Some studies strongly dispute the contribution of CFTR to organellar acidification, but others find that CFTR provides a counter-anion permeability that facilitates V-ATPase activity (16)(17)(18)(19)(20)(21). Estimates that minimal CFTR activity is required in the secretory pathway (66) are supported by studies showing that low-level transfection with recombinant CFTR corrects abnormal mucin sulfation without significantly increasing cAMP-stimulated Cl -permeability in CF airway epithelium (67).…”
Section: Discussionmentioning
confidence: 99%
“…organellar acidification by the vacuolar H + -ATPase (V-ATPase) (16). Others have both supported (17,18) and refuted (19)(20)(21) the contention that lysosomal/trans-Golgi pH is alkaline in CFTRdeficient cells. Recently, studies of human airway epithelium showed immunolocalization of CFTR with MUC5AC in isolated mucin granules and, further, demonstrated a CFTR-dependent Cl -conductance that enhanced granule acidification (22).…”
Section: Introductionmentioning
confidence: 99%
“…Lysosomal alkalinization decreased staining of Bodipy-pepstatin–A, suggesting the lysosomal enzyme cathepsin D was less effective in RPE cells with perturbed lysosomes [15, 16]. The clearance of outer segments is also decreased when the lysosomal pH is elevated with tamoxifen [17]. Thus experimental lysosomal alkalinization leads to decreased activity of degradative enzymes and accumulation of partially degraded photoreceptor outer segment debris.…”
Section: 3 Consequences Of Lysosomal Alkalinization On Degradationmentioning
confidence: 99%